2017
DOI: 10.18203/2394-6040.ijcmph20173318
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent anaemia its prevalence and determinants: a cross-sectional study from south Kerala, India

Abstract: Background: Anaemia is currently one of the most common and intractable nutritional problems globally. During the period of adolescence, iron requirements increase dramatically in both boys and girls resulting in a higher probability of anaemia. The objective of the study was done to find out the prevalence of anaemia among adolescent boys and girls in Ambalapuzha Taluk and to assess the scholastic performance of the anaemic and non-anaemic in the study group. Methods: The setting was different schools of Amba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
4
9
1
Order By: Relevance
“…is was consistent with findings reported in Tanzanian suburban areas which indicated adolescent anaemia of 14.5% and 7.9% for female and male, respectively [90]. e prevalence in this study is lower than that reported in India (62% females and 46.0% males were anaemic) [69] and Saudia Arabia (34.2% females and 16.7% males were anaemic) [91]. Anaemia causes are multifactorial but mainly is due to iron deficiency [20,90].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…is was consistent with findings reported in Tanzanian suburban areas which indicated adolescent anaemia of 14.5% and 7.9% for female and male, respectively [90]. e prevalence in this study is lower than that reported in India (62% females and 46.0% males were anaemic) [69] and Saudia Arabia (34.2% females and 16.7% males were anaemic) [91]. Anaemia causes are multifactorial but mainly is due to iron deficiency [20,90].…”
Section: Discussionsupporting
confidence: 91%
“…Micronutrient adequacy during adolescence is essential not only to support adolescents' health status but also to the future health in adulthood [ 68 , 69 ]. The increased demand for micronutrients during adolescence is contributed by a growth spurt and hormonal changes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the overall prevalence, the result of this study revealed that the prevalence of anemia was comparable to the other studies in Ethiopia including those conducted in Wonago Town [ 24 ] and Bonga Town [ 25 ]. On the other hand, the overall prevalence is much lower than the study conducted in India (62.0% in females and 46.1% in males, respectively) [ 29 ] and Chennai, Tamil Nadu, among adolescent female students which found 78.8% [ 30 ]. The difference in the finding of our study from different regions of the world could be due to the difference in cultural and behavioural practices in different areas of the world.…”
Section: Discussionmentioning
confidence: 94%
“…Another finding of a study conducted among adolescents in Wonago District, Gedeo Zone, Southern Ethiopia, found significantly higher prevalence of anemia among male adolescents (24.3%) than among female adolescents (18.1%) [ 24 ]. The finding from South Kerala in India also found that male adolescents were more anemic than female adolescents [ 29 ]. However, the finding of the study conducted in Bonga Town, Southwest Ethiopia, found that the prevalence of anemia among male adolescents was lower among males (9.4%) than females (19.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings and association was reported in the findings of Melwani et al, Soman et al who reported the prevalence of 175 and 18% in their study. 16,17 These findings suggest that parasitic infections and coexisting anaemia are significant health problem and need to be intervened with increasing awareness to increase the overall health and wellbeing of the tribal children.…”
Section: Discussionmentioning
confidence: 99%